Pathogenic determinants of Kingella kingae disease - Porsch, Eric A.; Hernandez, Kevin A.; Morreale, Daniel P.; Montoya, Nina R.; Yount, Taylor A.; St. Geme, Joseph W. (Frontiers in Pediatrics, 2022)
Kingella kingae is an emerging pediatric pathogen and is increasingly recognized as a leading etiology of septic arthritis, osteomyelitis, and bacteremia and an occasional cause of endocarditis in young children. The pathogenesis of K. kingae disease begins with colonization of the upper respiratory tract followed by breach of the respiratory epithelial barrier and hematogenous spread to distant sites of infection, primarily the joints, bones, and endocardium. As recognition of K. kingae as a pathogen has increased, interest in defining the molecular determinants of K. kingae pathogenicity has grown. This effort has identified numerous bacterial surface factors that likely play key roles in the pathogenic process of K. kingae disease, including type IV pili and the Knh trimeric autotransporter (adherence to the host), a potent RTX-family toxin (epithelial barrier breach), and multiple surface polysaccharides (complement and neutrophil resistance). Herein, we review the current state of knowledge of each of these factors, providing insights into potential approaches to the prevention and/or treatment of K. kingae disease.